Ecology and diversity in upper respiratory tract microbial population structures from a cross‐sectional community swabbing study. Issue 8 (August 2018) - Coughtrie, Abigail L.; Morris, Denise E.; Anderson, Rebecca; Begum, Nelupha; Cleary, David W.; Faust, Saul N.; Jefferies, Johanna M.; Kraaijeveld, Alex R.; Moore, Michael V.; Mullee, Mark A.; Roderick, Paul J.; Tuck, Andrew; et al.
Abstract : Purpose. : Respiratory tract infections (RTIs) are responsible for over 2.8 million deaths per year worldwide with pathobiont carriage a required precursor to infection. We sought to determine carriage epidemiology for both bacterial and viral respiratory pathogens as part of a large population‐based cross‐sectional carriage study. Methodology. : Nose self‐swab samples were collected in two separate time‐points, May to August 2012 (late spring/summer) and February to April 2013 (winter/early spring). The presence of six bacterial species: S. pneumoniae, H. influenzae, M. catarrhalis, S. aureus, P. aeruginosa and N. meningitidis in addition to respiratory syncytial virus, influenza viruses A and B, rhinovirus/enterovirus, coronavirus, parainfluenza viruses 1–3 and adenovirus was determined using culture and PCR methods. Results/Key findings. : Carriage was shown to vary with age, recent RTI and the presence of other species. Spatial structures of microbial communities were more disordered in the 0–4 age group and those with recent RTI. Species frequency distributions were flatter than random expectation in young individuals (X 2 =20.42, P =0.002), indicating spatial clumping of species consistent with facilitative relationships. Deviations from a neutral model of ecological niches were observed in summer samples and from older individuals but not in the winter or younger individuals (0–4 years), suggesting the presence of seasonal and age‐dependent niche processes in respiratory community assembly. Conclusion. : The application of epidemiological methods and ecological theory to respiratory tract samples has yielded novel insights into the factors that drive microbial community composition.